PERISTILAHAN RITUAL ADAT NGOJOK PADA MASYARAKAT DAYAK BANYADU - Daria, Evalisca; Amir, Amriani; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
This study aims to describe the traditional rituals term